(untitled) (New York, 2014)
Volume 85 presents an eclectic mix of articles of use to all human and molecular geneticists on topics including: association mapping in crop plants; miRNA-mediated crosstalk between transcripts; unisexual reproduction; and more.
Keywords: Plant genetics,Sinh học,Di truyền thực vật,Biology